PEMANFAATAN DIGITAL ENABLER DALAM TRANSFORMASI PEMASARAN DESA WISATA BERBASIS KERAKYATAN DI BALI - Bagus Putu Wahyu Nirmala; Sephy Lavianto (Jurnal Teknologi Informasi dan Komputer, 2019)
ABSTRACTTourism Village is believed to be a solution for destination management that is pro-community (community based tourism). On the island of Bali, there is a policy that aims to accelerate the development of tourist villages, namely Surat Edaran Kadisparda Nomor 556/317/I/DISPAR concerning the Development of 100 Tourism Villages in 2014-2018. Villages that has long been developed into a tourist village in Bali is Penglipuran Village and Taro Village.One of threat in the digital era, there has been a digitalization of business processes, including in the field of tourism village marketing, so innovation is needed in order to transform the tourism village marketing by utilizing digital enablers. Devices that are classified as digital enablers are mobile devices / mobile applications, internet of things, social media, QR codes and so on.This study focuses on utilizing digital enablers in order to transform marketing in two tourist villages, namely Penglipuran Village and Taro Village in the form of an application. It is expected that applications that empower digital enabler technology can help achieve five marketing functions of Digital Marketing Framework. The object of this research is marketing tourism villages in Bali with digital enablers using applications and integrating devices classified as digital enablers.Keywords: digital enabler, e-tourism, digital marketing framework, Bali village.ABSTRAKDesa Wisata diyakini menjadi solusi manajemen destinasi yang pro-masyarakat lokal (community based tourism). Di pulau Bali, ada kebijakan yang bertujuan untuk mempercepat pengembangan desa wisata, yaitu Surat Edaran Kadisparda Nomor 556/317 / I / DISPAR tentang Pengembangan 100 Desa Wisata di 2014-2018. Desa yang telah lama dikembangkan menjadi desa wisata di Bali adalah Desa Penglipuran dan Desa Taro. Salah satu ancaman di era digital, telah terjadi digitalisasi proses bisnis, termasuk di bidang pemasaran desa wisata, sehingga diperlukan inovasi dalam untuk mengubah pemasaran desa wisata dengan memanfaatkan digital enabler . Perangkat yang diklasifikasikan sebagai digital enabler adalah perangkat seluler / aplikasi seluler, internet, media sosial, QRcode, dan sebagainya. Studi ini berfokus pada pemanfaatan digital enabler untuk mengubah pemasaran di dua desa wisata, yaitu Desa Penglipuran dan Desa Taro dalam bentuk aplikasi. Diharapkan bahwa aplikasi yang memberdayakan teknologi digital enabler dapat membantu mencapai lima fungsi Kerangka Pemasaran Digital. Objek penelitian ini adalah pemasaran desa wisata di Bali dengan digital enabler menggunakan aplikasi dengan mengintegrasikan beberapa perangkat.Kata kunci: digital enabler, e-tourism, kerangka pemasaran digital, desa Bali.